Human-derived bacterial strains mitigate colitis via modulating gut microbiota and repairing intestinal barrier function in mice - Dai, Juanjuan; Jiang, Mingjie; Wang, Xiaoxin; Lang, Tao; Wan, Leilei; Wang, Jingjing (BMC microbiology, 2024)
Unbalanced gut microbiota is considered as a pivotal etiological factor in colitis. Nevertheless, the precise influence of the endogenous gut microbiota composition on the therapeutic efficacy of probiotics in colitis remains largely unexplored. In this study, we isolated bacteria from fecal samples of a healthy donor and a patient with ulcerative colitis in remission. Subsequently, we identified three bacterial strains that exhibited a notable ability to ameliorate dextran sulfate sodium (DSS)-induced colitis, as evidenced by increased colon length, reduced disease activity index, and improved histological score. Further analysis revealed that each of Pediococcus acidilactici CGMCC NO.17,943, Enterococcus faecium CGMCC NO.17,944 and Escherichia coli CGMCC NO.17,945 significantly attenuated inflammatory responses and restored gut barrier dysfunction in mice. Mechanistically, bacterial 16S rRNA gene sequencing indicated that these three strains partially restored the overall structure of the gut microbiota disrupted by DSS. Specially, they promoted the growth of Faecalibaculum and Lactobacillus murinus, which were positively correlated with gut barrier function, while suppressing Odoribacter, Rikenella, Oscillibacter and Parasutterella, which were related to inflammation. Additionally, these strains modulated the composition of short chain fatty acids (SCFAs) in the cecal content, leading to an increase in acetate and a decrease in butyrate. Furthermore, the expression of metabolites related receptors, such as receptor G Protein-coupled receptor (GPR) 43, were also affected. Notably, the depletion of endogenous gut microbiota using broad-spectrum antibiotics completely abrogated these protective effects. Our findings suggest that selected human-derived bacterial strains alleviate experimental colitis and intestinal barrier dysfunction through mediating resident gut microbiota and their metabolites in mice. This study provides valuable insights into the potential therapeutic application of probiotics in the treatment of colitis.